ANALISIS PENGARUH KARAKTERISTIK PERUSAHAAN, UKURAN DEWAN KOMISARIS DAN STRUKTUR KEPEMILIKAN TERHADAP PENGUNGKAPAN CSR (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2009-2011) - Laksmitaningrum, Chintya Fadila; Purwanto, Agus (Diponegoro Journal of Accounting, 2013)
This study aimed to analyze the effect of firm characteristics and ownership structure of a company, namely profitability, liquidity, leverage, firm size, board size, institusional ownership structure, managerial ownership structure, and foreign ownership structure of broad disclosure of corporate social responsibility.The population of this study is manufacturing company listed on the Indonesia Stock Exchange in the period 2009-2011. Sampling by using purposive sampling method,samples obtained amounted to 148 companies. Types of data used are secondary data with the method of documentation and literature method. The analytical tool used is multiple regression.This study found that profitability, liquidity, board size and structure of foreign ownership has a positive effect on disclosure of corporate social responsibility. However, leverage, firm size, institutional ownership structures and managerial ownership structure did not affect on disclosure of corporate social responsibility.